(untitled) (Research, Society and Development, 2020)
With the objective to evaluate the effects of regrowth period (14, 21, 28, 35 and 42 days) on green dry matter yield (GDMY), chemical composition and morphogenetic and structural characteristics of Brachiaria brizantha cv. Piatã, was carried out an experiment under greenhouse with natural conditions of light and temperature. GDMY yields and regrowth, leaf blade length, and leaf lifespan rate increased consistently (P<.05) with regrowth period, however the nitrogen, phosphorus, magnesium and potassium contents decreased as regrowth period, while calcium contents were not affected by regrowth period. Maximum GDMY, leaf appearance and elongation rate, and leaf blade length were obtained with regrowth periods at 38.2; 41.1; 31.3 and 38.9 days, respectively. These data suggest that cutting at 35 to 42 regrowth days were optimal for obtain maximum yields and regrowth of rich forage and pasture persistence.